WAYS OF REVIVAL OF UKRAINE'S ECONOMY IN THE POST-WAR PERIOD TAKING INTO ACCOUNT WORLDWIDE EXPERIENCE - CHORNII, Viktoriia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article analyzes the peculiarities of the current state of development of the economy of Ukraine. A review and assessment of the economic recovery of countries after military aggression was carried out. The key points in the formation of the recovery policy were highlighted on the example of the countries that were being rebuilt according to the Marshall Plan. The main directions of post-war recovery of countries such as Israel, South Korea, Japan, Italy, and West Germany were analyzed in detail and highlighted. It was established that, taking into account the fact that Ukraine has a powerful natural resource and intellectual and personnel potential, the main vectors in the direction of economic recovery for Ukraine in the post-war period are: the development of high technologies for production with high added value; forming the export orientation of the economy; development of infrastructural support, since Ukraine has a favorable geographical position, the development of the transport and communication structure will allow to develop the transit potential; use of intellectual and personnel potential in the development of high technologies, innovative production; activation due to state support of small business; changing the principles of implementing reforms of economic growth towards the activation of entrepreneurial initiatives and the attraction of foreign investors, while reducing the influence of the state on these processes; promoting the development of high-tech industries that use intellectual and innovative developments and have a high added value. The key directions for Ukraine were formed, which can be taken into account during recovery with adaptation to modern conditions of innovative development of the world economy. To determine the resource potential, the state and trends of the state's economic development were analyzed over the last period according to certain characteristics. Conceptual bases for the formation of a strategy for the development and restoration of the state in the post-war period are proposed.
Keywords: world experience of countries; post-war revival; potential of Ukraine; directions of post-war recovery